Multi-Excitation Signal for Depth Crack Defect in Eddy Current Testing - Kharudin, Ali; Abdalla, Ahmed N.; Damhuji, Rifai (2017)
Eddy current Non Destructive Evaluation (NDE) is one of the more commonly used techniques in measure electrical conductivity and thickness of plate and pipes. In recent years, several works have reported the sensitivity of probe in measuring the depth of crack according the input excitation. To extract relevant features for input excitation types of waveform, range frequency and depth of crack have been proposed. In this paper, a method to getting clear signal output for crack detection and data for differential depth of crack identified is reported. The measuring method Mulit-Excitation Signal (MES) is based on ac current signal, pulse signal and triangle signal. A frequency signal is set from 10KHz until higher 90KHz by following the probe’s limitation. Otherwise the calibration block is used as a defect plate with the depth of crack is 0.5mm, 1mm and 1.5mm. As a result the depth of cracks signal were clearly shown by using the three types of waveform with different levels of frequency and could be concluded when frequency of input excitation is high then the ability of signal to measure the crack on the material will decrease and if frequency is low then travelling signal in defect measuring is high but the responses time is low.